Nutrition communication from theory to practice: some future perspectives. - Rayner, M (2003)
'Nutrition communication' can be defined as the process by which nutrition knowledge is converted into dietary change. Nutrition communication then includes nutrition education--the process by which people are informed, and sometimes empowered by, nutrition information--but also other actions taken to improve peoples' diets such as restricting misinformation about nutrition or manipulating the composition, availability or price of foods. Dietary goals for populations and food-based dietary guidelines for individuals constitute the starting point for nutrition communication, and if these could be more evidence-based we would be in a much stronger position to develop more effective nutrition communication. A population-based approach to nutrition communication is complementary to an individualistic approach in theory, but in practice they compete for attention in food policy making circles.